Proposed new interior design of WWF·Information Centre for WWF·Malaysia at Lot 123 At Jalan Maarof, Bangsar Park 59000 Kuala Lumpur / Mohd Ameer Nicola Kasnin - Kasnin, Mohd Ameer Nicola (Faculty of Architecture, Planning and Surveying, 2010)
A requirement for an Interior design student, they have to do a project regarding the current issue to create a systematic building. Mays stages need to be through such as preliminary stage, schematic drawing stage and presentation stage. Students are also required to do case studies to understand the subject matter better. All stages will be practices when the student will be going out there to the real working environment. Thus, the design should be the best design that the student had learnt for about 3 years. For this project of Worldwide Fund Information Centre, the student has chosen to pick green issue as the main issue. This issue is also relating to the client. WWF or Worldwide fund has been working in conserving the environment since 1927. When it arrives in Malaysia, they have help keeping our beautiful rainforest from destruction of modern world. Since this project is a Green Design, the student are required to be more sensitive in designing the space so that it is comfortable yet less harmful than normal building in Malaysia.